Nicotinic receptor modulation to treat alcohol and drug dependence - Rahman, Shafiqur; Engleman, Eric A.; Bell, Richard L. (Frontiers in Neuroscience, 2015)
Alcohol and drug dependence are serious public health problems worldwide. The prevalence of alcohol and drug dependence in the United States and other parts of the world is significant. Given the limitations in the efficacy of current pharmacotherapies to treat these disorders, research in developing alternative pharmacotherapies continues. Preclinical and clinical evidence thus far has indicated that brain nicotinic acetylcholine receptors (nAChRs) are important pharmacological targets for the development of medications to treat alcohol and drug dependence. The nAChRs are a super family of ligand gated ion channels, and are expressed throughout the brain with twelve neuronal nAChR subunits (a2–a10 and b2–b4) identified. Here, we review preclinical and clinical evidence involving a number of nAChR ligands that target different nAChR subtypes in alcohol and nicotine addiction. The important ligands include cytisine, lobeline, mecamylamine, varenicline, sazetidine A and others that target a4b2* nAChR subtypes as small molecule modulators of the brain nicotinic cholinergic system are also discussed. Taken together, both preclinical and clinical data exist that support nAChR–based ligands as promising therapeutic agents for the treatment of alcohol and drug dependence.